Assessing the taxonomy of Heterometra-like feather stars (Echinodermata: Crinoidea: Himerometroidea) based on morphology and molecular data. Issue 7 (3rd October 2021) - Foo, Sze Hui; Taylor, Kristian H.; Messing, Charles G.; Rouse, Gregory W.; Tay, Teresa Stephanie; Tan, Koh Siang; Huang, Danwei
Abstract : The taxonomic classification of feather stars (Echinodermata: Crinoidea) has been unstable due to the extensive use of environmentally and ontogenetically variable morphological characters for diagnosing taxa. Furthermore, crinoids remain poorly studied even in some of the most biodiverse regions of the world, such as Southeast Asia. Historically, Heterometra (Comatulida: Himerometroidea: Himerometridae) has been the most abundant and speciose genus reported in Singapore, but species-level identification is challenging due to the lack of clear diagnostic features. In this study, the identities of 48 Heterometra -like crinoids collected from 21–64 m in southern Singapore were assessed based on detailed morphological examination and molecular phylogenetic inference. Specimens were initially grouped into three morphospecies, and phylogenetic analyses based on the cytochrome c oxidase subunit I gene placed these morphospecies in three distinct clades separated by large interspecific distances. Phylogenetic results coupled with additional examination of morphology confirmed the three morphotypes as Heterometra crenulata, Zygometra cf. comata, and H. schlegelii . The phylogeny further corroborates recent work showing that Heterometra is polyphyletic, with all examined species other than H. crenulata nested within the family Mariametridae, while Zygometra is nested in family Himerometridae. The separation of crenulata from other Heterometra and comparison of new material with type specimens lead us to treat this taxon as Homalometra crenulata comb. nov. and Ho. denticulata as its junior synonym. These findings highlight the need for a thorough revision of Himerometroidea.